Teachers’ digital literacy competencies according to their age status and their level of use in classes - Gökbulut Burak; Yeniasır Mustafa; Gökbulut Özlem Dağlı (SHS Web of Conferences)
Digital literacy means that individuals know how to properly use digital platforms/tools both for their personal development and for solving everyday problems, mastering information technologies and being aware of issues such as legal responsibility, data protection, security and ethics. In other words, people who are aware of their own and others’ privacy, security, and responsibility while using technological tools/applications and the Internet, and who use digital tools while maintaining their ethical attitude, can be called competent digital literacy. Otherwise, it is impossible to call people who take their phone or tablet in their hands and use digital media in a limited way (usually social media users) without being aware of any responsibility and completely open to threats. The study aims to reveal the digital literacy competencies of teachers according to age and their level of use in classes. A total of 50 primary and secondary school teachers make up the study’s sample. In this study, the mixed method was preferred to obtain more reliable results. In the mixed method research, while the numerical situation was revealed through quantitative data, they were strengthened with qualitative data. The “Digital Literacy Scale” was used to collect the quantitative data. This scale is a 5-point Likert-type tool and reveals the digital literacy status of teachers in a numerical sense. The qualitative data was collected using semistructured interview questionnaires created by the researchers based on expert opinions. While the quantitative data collected was statistically analyzed and interpreted, the qualitative data was analyzed using the descriptive analysis technique. According to the research findings, teachers are generally aware of the importance of digital literacy for education and training.